International Capital Markets : Developments, Prospects, and Key Policy Issues (September 1999). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
Following a review and assessment of recent developments in capital market and banking systems, this year's International Capital Markets report reviews and assesses recent developments in mature and emerging financial markets and continues the analysis of key issues affecting global financial markets. It examines the systemic implications of the continued rapid development of the global over-the-counter derivatives markets and the expansion of foreign-owned banks into emerging markets. The report also analyzes market participants' assessments of the proposals for private sector involvement in the prevention and resolution crises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet